Impact of low-carbon technologies on the power distribution network. (September 2019) - Rafi, A; Lee, T; Wu, W
Abstract: Over recent decades, there has been a growing concern about how modern technologies would impact on an electrical grid. Whilst the UK is set to meet the target of 15% energy demand from renewable sources by 2020 to ensure energy security and decarbonisation objectives, there has been a greater concern over how the increasing deployment of low carbon technologies (LCTs) would affect an electrical grid, in particular the residential low voltage distribution network. While LCTs can provide clean energy and decreases the dependence on oil and natural gas stocks, their impact on distribution networks is unknown and the operators are visibly blind as they use a 'fit and forget' approach. Consumers' connections are uncertain and stochastic and the LCT uptake poses a potential threat for distribution network operators. A review is presented in this paper, illustrating the potential impacts the LCTs have on a local electrical grid such as voltage regulation, thermal limits, power quality and harmonics. Potential solutions, such as Deregulation, Soft Open Points, On Load Tap Changer, and Active Power Filter currently available for Distribution Network Operators and power system planners before costly network reinforcement work is undertaken.